2020
DOI: 10.1002/jclp.23025
|View full text |Cite
|
Sign up to set email alerts
|

How much therapy is enough? The dose–response effect and its moderators in a psychology training clinic

Abstract: Objective: The current study aims to sharpen the understanding of the psychotherapy dose-response effect and its moderators in a psychology training clinic. Method: Data were extracted from 58 client records. Weekly Patient Health Questionnaire-9 and Generalized Anxiety Disorder-7, as well as Outcomes Questionnaire-45.2, administered every fifth session, assessed whether clients achieved reliable change (RC) and clinically significant and reliable change (CSR) during treatment. Survival analyses were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“… 19 Previous studies in higher income settings found that patients with higher levels of distress took eight more sessions to reach a similar recovery level than patients with lower levels of distress. 14 Some other studies found similar improvement ratios for patients with depression, namely 50% for the same range of 3–6 sessions, 34 while others reported a consensus of 25% improvement between sessions 3 and 4, and 50% between sessions 8 and 10. 33 , 35 Another study concluded that 40% of patients improved within two sessions, and up to eight sessions were necessary to achieve improvement in 60% of patients, but it did so without differentiating levels of severity.…”
Section: Discussionmentioning
confidence: 84%
“… 19 Previous studies in higher income settings found that patients with higher levels of distress took eight more sessions to reach a similar recovery level than patients with lower levels of distress. 14 Some other studies found similar improvement ratios for patients with depression, namely 50% for the same range of 3–6 sessions, 34 while others reported a consensus of 25% improvement between sessions 3 and 4, and 50% between sessions 8 and 10. 33 , 35 Another study concluded that 40% of patients improved within two sessions, and up to eight sessions were necessary to achieve improvement in 60% of patients, but it did so without differentiating levels of severity.…”
Section: Discussionmentioning
confidence: 84%
“…These findings suggest that clients with prior therapy may be more likely to terminate before achieving treatment goals, despite attending more sessions of therapy. Indeed, clients with prior therapy have been found to need more sessions to achieve reliable change (Chen & Keenan-Miller, 2020), therefore giving clients with prior therapy more opportunity to terminate prematurely.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, clients who perceived all previous therapy as helpful attended more sessions in this course of treatment than those who perceived all of their prior therapy as unhelpful. While this article argues that premature termination is best defined using a statistical measure of therapeutic change (i.e., RC or CSC), rather than the number of sessions attended by a client, we chose to examine how perceived helpfulness of prior therapy relates to the number of sessions attended to build upon prior work (e.g., Chen & Keenan-Miller, 2020) that has found it takes clients with prior therapy more time to achieve RC than clients with no prior therapy, and to shed light on how many sessions clinicians may have to increase engagement among clients who perceive some or all prior therapy as unhelpful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the above findings suggest support for effective treatment in a training clinic context, data on improvement trajectory within a treatment episode is more limited. One study recently evaluated the pattern of changes in depression, anxiety, and overall distress during psychotherapy within a training clinic (Chen & Keenan-Miller, 2021). The authors found that trainee-provided care yielded clinically significant change by Session 7–11 for 50% of their client population, although approximately 20 sessions were needed for 70% of the client population to yield such change.…”
Section: Literature On Client Outcomes In Training Clinicsmentioning
confidence: 99%